A review on techno-economic analysis of lignocellulosic biorefinery producing biofuels and high-value products - Ronak Patel; T.S. Rajaraman; Paresh H. Rana; Nikita J. Ambegaonkar; Sanjay Patel (Results in Chemistry)
Circular Bioeconomy (CBE) has gained momentum in recent years as an alternative to conventional energy sources. Cascaded use of wastes and residues has been seen as an attractive option with low environmental impact. Specifically, lignocellulosic biomass (LCB) promises to be a sustainable and abundant source of biomass. Numerous studies have been carried out with different LCBs to produce a host of biofuels and high-value products. Widespread research in the area has resulted in the development of novel conversion technologies of LCB into useful products. Despite the encouraging outcomes observed in laboratory-scale investigations, it is essential to conduct techno-economic analysis (TEA) on these processes to assess their viability for future commercialization. This review summarizes results from TEA studies on LCB-based biorefineries, with the main emphasis on biofuels (bioethanol, biohydrogen and biobutanol) and high-value products (xylitol, succinic acid, 5-HMF, and lactic acid). Effects of different parameters on the performance of LCB-based biorefineries have also been reviewed, which highlights its effect on plant economic indicators such as minimum selling price (MSP), capital expenditure (CAPEX), operating expenditure (OPEX), payback period (PBP) etc. Additionally, manufacturing of the above-mentioned biofuels and high-value products are discussed in brief along with challenges and possible solutions. TEA studies suggested that the MSP of biofuels, namely bioethanol (US$ 0.5–1.8/L) and biobutanol (US$ 0.5–2.2/kg), were competitive with their respective current market prices, whereas biohydrogen (US$ 9-33/kg) displayed a greater MSP. MSP of xylitol (US$ 1.5–3.1/kg), succinic acid (US$ 1.5–6.9/kg), 5-HMF (US$ 1–2/kg) and Lactic acid (US$ 0.5–1.9/kg) were competitive with their market price. Moreover, the synergetic effect of co-production was found to yield favourable economic outcomes. Key issues and opportunities for LCB-based biorefineries, in general, for CBE have also been addressed. Finally, the role of policy mechanisms, Artificial Intelligence (AI) and other data-driven technologies are also discussed in the biorefinery context.